Pembrolizumab Plus Ipilimumab or Placebo for Metastatic Non–Small-Cell Lung Cancer With PD-L1 Tumor Proportion Score ≥ 50%: Randomized, Double-Blind Phase III KEYNOTE-598 Study. Issue 21 (20th July 2021) - Boyer, Michael; Şendur, Mehmet A. N.; Rodríguez-Abreu, Delvys; Park, Keunchil; Lee, Dae Ho; Çiçin, Irfan; Yumuk, Perran Fulden; Orlandi, Francisco J.; Leal, Ticiana A.; Molinier, Olivier; Soparattanapaisarn, Nopadol; Langleben, Adrian; et al.
Abstract : PURPOSE: Pembrolizumab monotherapy is standard first-line therapy for metastatic non–small-cell lung cancer (NSCLC) with programmed death ligand 1 (PD-L1) tumor proportion score (TPS) ≥ 50% without actionable driver mutations. It is not known whether adding ipilimumab to pembrolizumab improves efficacy over pembrolizumab alone in this population. METHODS: In the randomized, double-blind, phase III KEYNOTE-598 trial (ClinicalTrials.gov identifier: NCT03302234 ), eligible patients with previously untreated metastatic NSCLC with PD-L1 TPS ≥ 50% and no sensitizing EGFR or ALK aberrations were randomly allocated 1:1 to ipilimumab 1 mg/kg or placebo every 6 weeks for up to 18 doses; all participants received pembrolizumab 200 mg every 3 weeks for up to 35 doses. Primary end points were overall survival and progression-free survival. RESULTS: Of the 568 participants, 284 were randomly allocated to each group. Median overall survival was 21.4 months for pembrolizumab-ipilimumab versus 21.9 months for pembrolizumab-placebo (hazard ratio, 1.08; 95% CI, 0.85 to 1.37; P = .74). Median progression-free survival was 8.2 months for pembrolizumab-ipilimumab versus 8.4 months for pembrolizumab-placebo (hazard ratio, 1.06; 95% CI, 0.86 to 1.30; P = .72). Grade 3-5 adverse events occurred in 62.4% of pembrolizumab-ipilimumab recipients versus 50.2% of pembrolizumab-placebo recipients and led to death in 13.1% versus 7.5%. The external data and safety monitoring committee recommended that the study be stopped for futility and that participants discontinue ipilimumab and placebo. CONCLUSION: Adding ipilimumab to pembrolizumab does not improve efficacy and is associated with greater toxicity than pembrolizumab monotherapy as first-line treatment for metastatic NSCLC with PD-L1 TPS ≥ 50% and no targetable EGFR or ALK aberrations. These data do not support use of pembrolizumab-ipilimumab in place of pembrolizumab monotherapy in this population.